DEVELOPMENT OF INFORMATIONAL AND COMMUNICATIVE COMPETENCE OF FUTURE ENGLISH LANGUAGE TEACHERS - Tursunov Shohruh Bahodir o‘g‘li (Journals Park Publishing, 2023)
The role of an English language teacher extends far beyond simply imparting knowledge of the language. English language teachers are tasked with developing their students' ability to communicate effectively in English, navigate its cultural nuances, and become confident language users. To achieve this, future English language teachers must develop informational and communicative competence. This article explores the essential aspects of cultivating these competencies to empower teachers to excel in their roles and, in turn, empower their students.
Keywords: informational competence, communicative competence, language teachers, language proficiency, confident users.